2016
DOI: 10.1007/s10461-016-1503-x
|View full text |Cite
|
Sign up to set email alerts
|

Partner-Level Factors Associated with Insertive and Receptive Condomless Anal Intercourse Among Transgender Women in Lima, Peru

Abstract: Condomless anal intercourse among transgender women (TW) in Peru has been shown to vary by the type of partner involved (e.g. primary vs. casual vs. transactional sex partner), but no previous studies have explored variations in partner-level patterns of condom use according to type of anal intercourse. We evaluated the relationship between partnership characteristics and condom use during insertive (IAI) versus receptive anal intercourse (RAI) among TW with recent, non-female partners. Condomless IAI was more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
(65 reference statements)
1
6
0
2
Order By: Relevance
“…Partnership type was the only partnership-level characteristic found to be significantly associated with both condomless receptive anal intercourse (CRAI) and condomless insertive anal intercourse (CIAI), with participants reporting significantly lower odds of CRAI and CIAI in casual and commercial partnerships compared with main partnerships. Similar to studies of adult transwomen, MSM and a previous study of young transwomen,6 7 W3 W5 we found a significantly higher risk of having condomless anal intercourse with main partners. Among MSM, main partners are believed to be the principal source of HIV transmission because of a higher number of sex acts, a higher frequency of receptive roles during anal sex and lower condom use.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Partnership type was the only partnership-level characteristic found to be significantly associated with both condomless receptive anal intercourse (CRAI) and condomless insertive anal intercourse (CIAI), with participants reporting significantly lower odds of CRAI and CIAI in casual and commercial partnerships compared with main partnerships. Similar to studies of adult transwomen, MSM and a previous study of young transwomen,6 7 W3 W5 we found a significantly higher risk of having condomless anal intercourse with main partners. Among MSM, main partners are believed to be the principal source of HIV transmission because of a higher number of sex acts, a higher frequency of receptive roles during anal sex and lower condom use.…”
Section: Discussionsupporting
confidence: 89%
“…Sexual networks may, in part, explain the high prevalence of HIV among transwomen 4 5. Studies with adult transwomen and men who have sex with men (MSM) found that main partnerships, seroconcordance, racial concordance and injection drug use discordance to be associated with greater sexual risk taking behaviours 5–8. Additionally, greater age discordance between sexual partners has been associated with increased HIV risk in cisgender heterosexual women and MSM 9 10…”
Section: Introductionmentioning
confidence: 99%
“…All participants were recruited by staff at the Asociación Civil Impacta Salud y Educación [“Impact Health and Education” Civil Association] in Lima and the Centro de Referencia de ITS [STI Referral Center] “Alberto Barton” in Callao as part of a 2012 study of MSM and TW recently diagnosed with HIV and/or another STI. Participant recruitment, data collection methods, and data instruments have been previously described [21, 22]. Briefly, enrollment was limited to individuals who: 1) Were assigned male sex at birth, while some identified as cisgender men (gender identity congruent with natal sex) or as TW (assigned male sex at birth and reporting gender identity on a transfeminine spectrum), 2) Reported anal or oral intercourse with a male or TW partner during the previous year, and 3) Had been diagnosed within the previous 30 days with HIV, syphilis, genital herpes, urethritis or proctitis.…”
Section: Methodsmentioning
confidence: 99%
“…Esto puede tratarse de acuerdos sexuales 37 entre las parejas, y también un reflejo de cómo ellas se perciben y cómo se ha introyectado la hetero-cisnormatividad en sus formas de socialización y de experimentar su sexualidad. La hetero-cisnorma cumple su cometido al hacerles sentir que "no son mujeres", no como "las demás", que sus cuerpos son ajenos a lo que el género como estructura dicta.…”
Section: El Género Y El Vih En Las Relaciones Interpersonalesunclassified